Does customised care improve satisfaction and positively enable parents in sustained home visiting for mothers and children experiencing adversity? - Kie Kanda; Stacy Blythe; Rebekah Grace; Emma Elcombe; Lynn Kemp (BMC, 2022)
Abstract Background The Maternal Early Childhood Sustained Home-visiting program (MECSH) is a structured nurse-delivered program designed to address health inequities experienced by families experiencing significant adversity. There is strong evidence for the effectiveness of this program, but limited research exploring the practice and process elements that are core to positive parent outcomes. This study aimed to examine the relationship between customised care related to the mother's risk factors and parent satisfaction and enablement in the delivery of a MECSH-based program. Methods A cross-sectional study design was used. Program delivery data collected as part of a large randomised controlled trial of a MECSH-based sustained nurse home visiting program in Australia (right@home) were analysed. This study used the data collected from the intervention arm in the trial (n = 352 women). Parent satisfaction was measured at child age 24 months using the modified short-form Patient Satisfaction Questionnaire. Parent enablement was measured at child age 24 months by a modified Parent Enablement Index. Customised care was defined as appropriate provision of care content in response to four maternal risks: smoking, mental health, domestic violence and alcohol and drugs. Logistic analysis was performed to assess the impact of customised care on parent satisfaction and enablement while adjusting for covariates such as sociodemographic factors. A significance level of 95% was applied for analysis. Results Our results indicated high levels of satisfaction with the care provided and positive enablement. There were several sociodemographic factors associated with satisfaction and enablement, such as language spoken at home and employment experience. The mothers who received customised care in response to mental health risk and domestic violence had significantly greater satisfaction with the care provided and experienced an increase in enablement compared to those who did not receive such care. Conclusion This study contributes to the existing body of empirical research that examines the relationship between care processes and client outcomes in the delivery of home visiting services. It is essential for the sustained nurse home visiting service model to be flexible enough to cater for variations according to family circumstances and needs while maintaining a core of evidence-based practice.